Cigarette smoking and small irregular opacities. Issue 12 (December 1991) - Weiss, W
Abstract : A survey of chemical workers by chest roentgenograms was designed to determine whether exposure to acrylic dust and/or cigarette smoking was associated with diffuse abnormalities suggestive of pneumoconiosis. The films were examined without knowledge of dust exposure or smoking habits. The International Labour Office (ILO) classification and standard films were used. Workers with exposure to asbestos were excluded. There was no relation between prevalence of abnormalities and exposure to dust. Among 181 workers 28 had s and/or t small irregular opacities with profusion of 0/1 (23), 1/0 (three), or 1/1 (two). These findings were present in 20% of smokers compared with 2.2% of non-smokers. The prevalence increased with increasing age to 31.6% among smokers aged 50-64. Prevalence was 10% among ex-smokers of cigarettes. Among current cigarette smokers, prevalence was 5.3% in those who smoked less than one pack per day, 31.3% in heavier cigarette smokers, and 52.9% in 17 heavy cigarette smokers aged 50-64. Profusions of 0/1 and 1/0 are classified as "suspect" pneumoconiosis according to the ILO guidelines. The data in this study indicate that such abnormalities are directly related to age and smoking habits among workers not exposed to hazardous dust.